Percutaneous Image-Guided Cryoablation of Recurrent Myxofibrosarcoma in the Forearm: A Case Report and Review of Literature - Milin Patel; Jason Manaparambil; Indravadan J. Patel (Journal of Clinical Interventional Radiology ISVIR)
Myxofibrosarcoma (MFS) is a rare, aggressive soft tissue sarcoma with high recurrence rates. Conventional treatment involves wide surgical resection and radiotherapy, but the infiltrative nature of MFS often complicates complete resection. This case highlights an 81-year-old patient with recurrent MFS in the left forearm, initially treated with surgery and radiation therapy. Due to surgical limitations and desire for a minimally invasive approach after recurrence, cryoablation was performed. The patient underwent the procedure successfully, and postoperative imaging indicated effective ablation. This case demonstrates cryoablation as a feasible, minimally invasive alternative for managing recurrent MFS, particularly in anatomically challenging cases.